Aprendizagem potencialmente significativa de Geometria Molecular por Simulação Digital - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The learning of Chemistry, over the years, has undergone great transformations, this is due to the fact of seeking new teaching alternatives in order to favor the construction of knowledge, avoiding a simple memorization of contents. Materials that are potentially significant for teaching are those that are relatable to or incorporate into the student’s cognitive structure, in a non-arbitrary and non-literal way, promoting the process of meaningful learning. In this sense, the objective of this work is to develop a potentially significant didactic-pedagogical approach based on the Ausubelian conception, with the use of computer simulation aided by the Information and Comunication Digital Technologies (ICDT’s) as potentially significant material for learning molecular geometry. This approach enables the use of several strategies and subsumer concepts for Molecular Geometry, facilitating learning and making it meaningful. The research was based on an experimental qualitative approach, with data collected through diagnostic questionnaires, narratives and learning verification exercises in a regular Public High School located in the southern zone of the city of Manaus, with the participation of 10 students of the 1st year volunteers, whose results were evaluated by content analysis. In the results, it was possible to identify through Ausubel's theory, that significant learning pointed to two forms: subordinate and superordinate. It was verified, therefore, that there was a better performance of the students participating in the research in the first three questions of the post-simulator questionnaire and evidence of learning with characteristics of progressive differentiation and integrative reconciliation in the last two questions. The results show that computer simulation is a very effective technological tool, which generates dynamic and significant learning, especially in the new pandemic scenario of the new coronavirus (SARS-COV2), where we had to reinvent ourselves in the face of so many uncertainties and adversities.
Potentially Meaningful Learning of Molecular Geometry by Digital Simulation
Keywords: Química - Aprendizagem; CIENCIAS EXATAS E DA TERRA: QUIMICA; Aprendizagem de Química; Geometria Molecular; Simulação Digital; Tecnologias Digitais de Informação e Comunicação; Aprendizagem Significativa